Exploring Short Story as Learning Media for Teaching Intensive Reading to 11th Grade English Students - Saputra, Andieny Ratu; Nanda, Deri Sis (Indonesian Journal of Teaching and Learning, 2026)
Purpose – This study aims to explore the use of short stories as a teaching and learning medium in an intensive reading class for eleventh-grade students at SMA Al Azhar 3, Bandar Lampung. The background of this study is the need for engaging reading materials that can improve students’ comprehension, analytical skills, and motivation in intensive reading activities. Methodology - The study employed a qualitative research design. The sample consisted of eleventh-grade students from SMA Al Azhar 3 in Bandar Lampung, selected through purposive sampling. Data were collected through classroom observations and questionnaires. The research procedure involved implementing short stories as instructional media in intensive reading lessons. The instruments used were observation sheets and student questionnaires, and the data were analyzed descriptively to identify patterns in students’ engagement, comprehension, and responses. Findings – The findings indicate a significant improvement in students’ ability to engage with and comprehend intensive reading activities through the use of short stories. Students showed better understanding of storylines, enhanced analytical skills, and increased participation during lessons. However, the study did not measure the long-term effectiveness of short stories as a teaching tool. Novelty – This research offers original insights into the use of short stories as an instructional medium for intensive reading at the senior high school level, highlighting students’ cognitive and affective responses in a real classroom context. Significance – The findings of this study are beneficial for English teachers, curriculum developers, and educational practitioners who seek effective and engaging strategies for teaching intensive reading.